Differences in selected blood parameters between brachycephalic and non-brachycephalic dogs - Kämpf, Sandra; Fenk, Simone; Van Cromvoirt, Ankie; Bogdanov, Nikolay; Hartnack, Sonja; Stirn, Martina; Hofmann-Lehmann, Regina; Reichler, Iris Margaret; Bogdanova, Anna (Frontiers in Veterinary Science, 2023)
Cranial and upper-airway anatomy of short-nosed flat-faced brachycephalic dogs predisposes brachycephalic obstructive airway syndrome (BOAS). Periodic apnoea increased inspiratory resistance and inability to thermoregulate effectively are characteristic for BOAS, but internationally accepted objective markers of BOAS severity are missing. The objective of this study was to compare the selected blood parameters between non-brachycephalic (NC) and brachycephalic (BC) dogs, exploring the possibility to develop a blood test for BOAS severity grading in the future. We evaluated blood biochemistry, complete blood cell counts, red blood cell (RBC) indices, reticulocyte counts, a bloodborn marker of intermittent hypoxia (glutathione, NO production), RBC hydration, deformability, and blood markers of metabolic changes and stress between BC (n = 18) and NC (meso-and dolichocephalic, n = 22) dogs. Reticulocyte counts and the abundance of middle-fluorescence immature reticulocytes were significantly (p<0.05) higher in BC dogs compared to NC dogs. BC dogs had significantly more NO-derived NO2 -/NO3 -in plasma than NC dogs. RBCs of BC dogs were shedding significantly more membrane as follows from the intensity of Eosin maleimide staining and had significantly higher mean corpuscular hemoglobin concentration than NC dogs. Intracellular reduced glutathione content in RBCs of BC dogs was significantly lower, while plasma lactate was significantly higher in BC dogs compared to NC dogs. Plasma cholesterol and triglyceride were significantly lower, and cortisol was significantly higher in BC dogs compared to NC dogs. Eosinophil counts were significantly lower and the neutrophil-to-lymphocyte ratio higher in BC dogs compared to NC dogs. Taken together, our findings suggest that brachycephalic phenotype in dogs is associated with alterations at the level of blood cells and, systemically, with oxidation and metabolic changes. The parameters identified within this study should be further investigated for their potential as objective indicators for BOAS.